Culture of Movement Awareness through Physical Literacy Integrated in Physical Education, Physical Activity and Sport during COVID-19: Systematic Literature Review - Ruslan Abdul Gani; Edi Setiawan; Novri Gazali; Zsolt Németh; Irfan Zenat Achmad; Firman Septiadi; Jeki Haryanto (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose: A culture of movement awareness through physical literacy in physical education, physical activity and sports is a core aspect that must be promoted continually during the current COVID-19 pandemic. This study aims to conduct a literature review regarding the importance of a culture of movement awareness through physical literacy in physical education, physical activity and sports. Material and Methods: This study used a Systematic Literature Review with Preferred Reporting Item for Systematic Reviews and Meta-Analytic method. There was 4 Stages in collecting data using a database search, namely through Sage Pub, Eric, Pubmed and Sciencedirect. This study adopted 7 international journal articles indexed by Scopus Q1. Results: The results of this study found that a culture of movement awareness through physical literacy which was integrated into physical education, physical activity and sports had a major contribution in creating active participation to lead a healthy life  during the pandemic. Conclusions: Therefore, maintaining and increasing a culture of movement awareness through physical literacy during the COVID-19 period in various settings is the key in maintaining the health status of people around the world